Konsep Islam Tentang Ekonomi - Ahmad Adnan (STID DI AL-HIKMAH, 2015)
The human need for completeness means of life of primary needs, tertiary and luxury goods or other terms dhoruriyyat, hajiyat and tahsiniyyat well as clothing, clothes, housing, vehicles and completeness of its life, this is all said the needs of the economy, and that is called economy. To produce, own and utilization of so-called economic necessities of life are not free to menghalalakan immediately Asaal way and I can careless hurt people or not important success has, once again do not like it, Islam the source of the Qur'an and Assunnah and ijma scholars come to put restrictions, standards and rules, the basics: good, lawful, not goror, unlawful, doubtful, zholim menzholimi, slather-waste in and moderation.